Women with disabilities: policies governing procedure and practice in service provision in Ireland during pregnancy, childbirth and early motherhood. - BEGLEY, CECILY; NICHOLL, HONOR; LAWLER, DENISE; LALOR, JOAN; HIGGINS, AGNES (National Disability Authority, 2009)
This review was commissioned by the National Disability Authority (NDA), in a joint initiative with the National Women?s Council of Irelan d (NWCI), to provide comprehensive information on social policies, relating t o disability and childbirth, both in Ireland and internationally. The review is one of 3 documents meeting the objectives of a nation-wide study commissioned by the ND A. It is recommended that readers also consult the other 2 reports, a comprehensive literature review of Irish and international literature on the challenges facing women with physical, sensory, mental health or intellectual disabilities in accessing h ealth services during pregnancy, childbirth and early motherhood (Begley e t al, 2009) and a presentation of findings of a nation-wide study exploring the stren gths and weaknesses of publicly- funded Irish health services provided to women with disa bilities in relation to pregnancy, childbirth, and early motherhood (Begley e t al, 2010).
PUBLISHED
Dublin
Keywords: Midwifery